(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
This study delves at the intents and ability of women business owners from Madhya Pradesh to launch their own firms while juggling job and family responsibilities. Indore, Bhopal, and Jabalpur, the three largest entrepreneurial centres in the state, were evaluated using a standardised 5-point Likert scale questionnaire. Three hundred and fifty female business owners took part. Both descriptive and inferential statistics were conducted using SPSS 21 in this study. We used reliability, factor, correlation, and one-way ANOVA as our descriptive statistics. The statistical robustness of the instrument is shown by its outstanding sampling (KMO = 0.929; Bartlett's Test p < 0.001) and great internal consistency (Cronbach's Alpha = 0.942). Improving women-led enterprises requires empowering women financially, since work-life balance and entrepreneurial drive are greatly influenced by economic factors (F = 61.23, p < 0.001; r = 0.456). Individual and vocational characteristics, as opposed to family variables, have a greater impact on self-regulation and adaptation. Women report higher levels of happiness and success when they are financially independent and have the support of their families. The results of this research provide credence to a model that attempts to explain the effects of familial and socioeconomic factors on the entrepreneurial success of women in regional markets. For the benefit of women entrepreneurs in Madhya Pradesh, policymakers should encourage the formation of family networks, simplify the process of taking out loans, and highlight the importance of personal finance.